GPGPU: Hardware/Software Co-Design for the Masses - Mann, Zotlán Ádám (Computing and Informatics, 2012)
With the recent development of high-performance graphical processing units (GPUs), capable of performing general-purpose computation (GPGPU: general-purpose computation on the GPU), a new platform is emerging. It consists of a central processing unit (CPU), which is very fast in sequential execution, and a GPU, which exhibits high degree of parallelism and thus very high performance on certain types of computations. Optimally leveraging the advantages of this platform is challenging in practice. We spotlight the analogy between GPGPU and hardware/software co-design (HSCD), a more mature design paradigm, to derive a design process for GPGPU. This process, with appropriate tool support and automation, will ease GPGPU design significantly. Identifying the challenges associated with establishing this process can serve as a roadmap for the future development of the GPGPU field.